2011
DOI: 10.1073/pnas.1111492108
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body deletion of LPS-induced TNF-α factor (LITAF) markedly improves experimental endotoxic shock and inflammatory arthritis

Abstract: LPS-induced TNF-α factor (LITAF) mediates cytokine expression in response to endotoxin challenge. Previously, we reported that macrophage-specific LITAF-deficient (macLITAF −/− ) mice exposed to LPS have a delayed onset in the serum levels of proinflammatory cytokines and prolonged persistence of anti-inflammatory cytokines, but only partial protection from endotoxic shock. We postulated that greater protection might be achieved if LITAF were deleted from all LITAF-producing cells, including macrophages. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 34 publications
(37 reference statements)
1
29
0
Order By: Relevance
“…4A) (34,37). Lastly, SIMPLE is also known as LITAF, which is induced upon inflammation and modulates cytokine gene induction (54)(55)(56). Together, these observations strongly suggested that SIMPLE might play a role in ubiquitin-mediated inflammatory signaling.…”
Section: T115n/t115nmentioning
confidence: 71%
See 2 more Smart Citations
“…4A) (34,37). Lastly, SIMPLE is also known as LITAF, which is induced upon inflammation and modulates cytokine gene induction (54)(55)(56). Together, these observations strongly suggested that SIMPLE might play a role in ubiquitin-mediated inflammatory signaling.…”
Section: T115n/t115nmentioning
confidence: 71%
“…In addition, Tom1, which interacts with SIMPLE and was proposed as an ancestral type ESCRT-0 (91,92), facilitates the internalization and termination of the activated TLR complex and the TNF-␣ receptor (93). Furthermore, previous reports showed that SIMPLE-null mice are less sensitive to challenge by a lethal dose of LPS, in part due to altered cytokine levels (54,56,94). Thus, we expect a similar role for SIMPLE in the TLR complex and the TNF-␣ receptor signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli LPS (100μg/mouse) every three days; and 3. Kavain (1~1.2mg/ mouse) every other day [10, 27] in a 10-day experimental protocol. Arthritis was monitored using a clinical score and later by histological analysis of hind dorsal paws.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of E. coli LPS on transcription factor activity and expression have been widely investigated [10]. We cloned E. coli LPS Induced TNF-Alpha Factor (LITAF) [11], and showed that it partially controls TNF-α gene expression [12, 13].…”
Section: Introductionmentioning
confidence: 99%